1966
DOI: 10.1063/1.1708518
|View full text |Cite
|
Sign up to set email alerts
|

Measured Relaxation Times for the Uniaxial-Anisotropy Spectrum in Nonmagnetostrictive Permalloy Films

Abstract: The relaxation time τ for realignment of an atomic anisotropy by 90° has been measured for a number of fast processes (τ<103 sec) occurring in nonmagnetostrictive Permalloy films. The method of measurement utilizes the magnetoresistance effect and is described in detail elsewhere. For films deposited between 23° and 200°C at 10−6 to 10−5 Torr and measured at the same temperature and pressure, three distinct processes plus two probable ones have been found, which together account for about one-quarter of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1966
1966
2003
2003

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…This study was motivated by reports that the induced anisotropy of thin films may change upon annealing in a magnetic field, even at temperatures in the order of 100-200°C. [17][18][19][20] Indeed, we observed that ⌬H s may change dramatically when the spin valves are subjected to elevated temperatures. This is relevant from an applications point of view, since process steps at a temperature of 150-200°C are very common in the fabrication of magnetoresistive sensing devices.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…This study was motivated by reports that the induced anisotropy of thin films may change upon annealing in a magnetic field, even at temperatures in the order of 100-200°C. [17][18][19][20] Indeed, we observed that ⌬H s may change dramatically when the spin valves are subjected to elevated temperatures. This is relevant from an applications point of view, since process steps at a temperature of 150-200°C are very common in the fabrication of magnetoresistive sensing devices.…”
Section: Introductionmentioning
confidence: 93%
“…In Fig. 5, the 18 Co 12 -layer thickness. So the increase in coupling strength with increasing thickness of the sensitive layer is entirely ascribed to the evolution of the lateral length scale of the roughness.…”
Section: ͑3͒mentioning
confidence: 99%
See 1 more Smart Citation